(untitled) (AIUB Journal of Science and Engineering (AJSE), 2025)
With the increasing integration of photovoltaic (PV) systems into power grids, Low Voltage Ride-Through (LVRT) capability has become crucial for maintaining grid stability and reliability. Existing LVRT strategies often struggle with asymmetrical faults, leading to DC-link voltage fluctuations and inadequate reactive power support. This study proposes an improved integrated control method to enhance the LVRT capability of grid-tied PV systems during asymmetrical disturbances. The control strategy integrates DC-link voltage regulation, reactive power injection, and voltage sag compensation, considering both balanced and unbalanced fault conditions. A PI controller with cascaded control with feed-forward decoupling in the current loop is implemented for improved current control, while a Synchronous Reference Frame Phase-Locked Loop (SRF-PLL) ensures grid synchronization. This integrated approach offers advantages in system stability, rapid fault response, and grid code compliance. Simulation results for a 1.5 MW PV plant demonstrate the control’s effectiveness, reducing grid voltage sag by 96.5%, injecting up to 78% of reactive power, and maintaining DC-link voltage within acceptable limits during Line-to-line faults.